Databases theory and applications : 27th Australasian Database Conference, ADC 2016, Sydney, NSW, September 28-29, 2016, proceedings /: 27th Australasian Database Conference, ADC 2016, Sydney, NSW, September 28-29, 2016, proceedings. (2016) - Unknown
No abstract available